Carbon emission from vehicular source in selected industrial areas in Malaysia - Azliyana Azhari,; Ahmad Fariz Mohamed,; Mohd Talib Latif, (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
Vehicle emission has been the major source of environmental pollution for the past 30 years. The urbanization, industrialization and traffic systems growth are causing more air pollution problem in the city creating an uncomfortable atmosphere to live in. Carbon emission is one of the main air pollutants causing problems in the local and global community. This paper discusses the effect of increasing vehicular traffic on the road in a few industrial sites within cities in Malaysia to the release of carbon dioxide and carbon monoxide in the atmosphere. This paper studies the traffic trend using census data from JKJR and converted into carbon emission using DEFRA GHG Conversion Factors and air quality trend from Alam Sekitar Malaysia in three selected industrial area in Malaysia, which are Shah Alam Industrial Area, Seremban-Senawang Industrial Area and Kuantan-Pekan Industrial Area. Carbon monoxide concentration trend in Shah Alam and Seremban-Senawang fluctuates with the highest concentration of 1.78ppm for Shah Alam and 0.77ppm in Seremban-Senawang in the earlier years and becoming lower in 2010 and 2011 compared to the trend in Kuantan-Pekan, which increased since 2001 to 2011 with the highest concentration of 0.54ppm. Carbon dioxide concentration is highest at Shah Alam ranging from 18067.17 to 88150.01 kg CO2 /km travelled compared to Kuantan-Pekan ranging from 3520.39 to 6953.69 kg CO2 /km travelled and Seremban-Senawang ranging from 3783.29 to 5734.30 kg CO2 /km travelled. Based on the early findings, the increasing vehicular traffic resulted in increment of carbon emission in the atmosphere.